Primary staging with 2[18F]-FDG-PET/CT and -PET/MRI and radiotherapy response evaluation with MRI in uterine cervical cancer: an interim analysis of a prospective clinical trial - Maja Aasa; David Lindquist; Ulrika Ottander; Sara N. Strandberg (EJNMMI Reports)
Abstract Background In uterine cervical cancer (UCC), tumour staging is performed according to the 2018 International Federation of Gynecology and Obstetrics (FIGO) system, where imaging is incorporated, or the more generic Tumour Node Metastasis (TNM) classification. With the technical development in diagnostic imaging, continuous prospective evaluation of the different imaging methods contributing to stage determination is warranted. The aims of this interim study were to (1) evaluate the performance of radiological FIGO (rFIGO) and T staging (rT) with 2-fluorine-18-fluoro-deoxy-glucose (2[18F]-FDG)-positron emission tomography with computed tomography (PET/CT) and with magnetic resonance imaging (PET/MRI), compared to clinical FIGO (cFIGO) and T (cT) staging based on clinical examination and conventional imaging, in treatment-naïve UCC, and to (2) identify possible MRI biomarkers for early treatment response after radiotherapy. Methods Ten consecutive patients with newly diagnosed UCC from the prospective PRODIGYN (Prognostic and Diagnostic Added Value of Medical Imaging in Staging and Treatment Planning of Gynecological Cancer) study (ethical approval number 2022-04207-01; NCT05855941) were included. Study participants underwent 2[18F]FDG-PET/CT and -PET/MRI, and an additional MRI one week after radiotherapy. Agreement between rFIGO and cFIGO was analysed using Cohen’s kappa. Differences in rFIGO between 2[18F]FDG-PET/CT and -PET/MRI were evaluated with Wilcoxon signed ranks test, and added value of rFIGO for metastasis assessment was demonstrated with descriptive statistics. Results In 2/10 patients, a higher stage was obtained with rFIGO compared to cFIGO, where presence of metastases led to upstaging. In 3/10, rFIGO was lower than cFIGO, and in 5/10 rFIGO and cFIGO were similar. Degree of agreement between rFIGO and cFIGO was poor, (κ = 0.091, p < 0.005) with 2[18F]FDG-PET/CT and (κ = − 0.010, p > 0.05) with FDG/PET/MRI). There was no significant difference between 2[18F]FDG-PET/CT and -PET/MRI for rFIGO (p = 0.18), or rT stage assessment (p = 0.32). MRI-derived tumour volume and apparent diffusion coefficient (ADC) were most affected on MRI one week after radiotherapy. Conclusions Our results indicate that there is an added value of rFIGO staging with 2[18F]FDG-PET/CT and -PET/MRI compared to clinical examination and conventional radiology, for metastasis assessment in treatment-naïve UCC. In early treatment response evaluation with MRI, ADC and tumour volume may be predictive parameters of interest in future prognostic analyses. Trial registration Clinical Trials, NCT05855941. Registered 02 May 2023, https://clinicaltrials.gov/study/NCT05855941?term=NCT05855941&rank=1 .